Surgical Repair of Recto-Vaginal Tear from Dystocia in a Thoroughbred Mare: A Case Report - Malapolu, Shantha Vardhan; Maribasaviah, Dinesh Nanjappa; Adsul, Manojkumar; Jayanna, Renukaradhya Gudepalya; Sali, Abhilash Babu (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Rectovaginal fistula (RVF) is an abnormal communication between the rectum and vagina, often resulting from foaling trauma in mares, such as dystocia caused by malpositioned foals (Pooniya et al., 2019). The injury is seen predominantly in primiparous mares and is usually due to violent expulsive efforts by the mare (Colbern et al., 1985; Turner and McIlwraith, 1989). This condition risks reproductive tract infections, potentially impairing fertility, a critical concern for Thoroughbred breeding farms (LeBlanc, 2010). In India, where Thoroughbreds are bred under live cover regulations and tropical conditions, RVF management is vital to minimize economic losses (Scoggin et al., 2015). Surgical repair, typically using layered suturing, is the standard treatment, with reported high success rates (Easley, 1988; Jalim and McKinnon, 2010). This case report describes the successful surgical correction of a recto-vaginal tear in a primiparous Thoroughbred mare from stud farm, Karnataka, aiming to highlight effective management strategies and their relevance to India’s equine industry.